Terror ecranovision in XXI Century - Rodrigues Costa, Pedro (2012)
One of the most powerful ecranovisions of the screens history, it happened in 2001: The Nine Eleven. In this article, analyzing qualitative interviews, we reveal how this ecranovision, since that day to the present, is still the archetype of terror in those who were his subjects. We conclude that, at the exact moment, the media event is especially true for the violent force of the timeliness; after this, takes effect by its strength in ecranovision mode, that is, its ability to impose itself in the consciousness, and individual and collective contingencies. This is an example of the strength of ecranovisions, something that here we want to reveal.